JARINGAN TEKNOLOGI FATMA PADA SISTEM KOMUNIKASI SATELIT PERMINYAKAN (SKSP) PERTAMINA UPPDN VII MAKASSAR - Amir, Ardi (MEKTEK, 2012)
FATMA Technology (Frequency And Time Multiple Access) is a form of progress of FDMA and TDMA are combined into one in which on one network can use up to 32 carrier frequencies (frequency division), and on each carrier should ideally be occupied by 32 nodes / stations simultaneously (time division).Technology in Indonesia Fatma access methods specifically used by Pertamina Oil Satellite Communication System (SKSP) in order to better communication between and among all units of the existing branches. In this study conducted an analysis of a network using the system point to point communication link between one point with another point of direct and multi-point systems and communication links with the mesh provided by ACT-ONE modem that uses Fatma. The pattern of relationships / mesh topology is that each station can be connected directly by using a single hop.Selain was also described on network analysis.